Effect of spectral quality on plant development of Salvia splendens variety Vista Red and White - Gómez-Coto, Federico José (2014)
Three different qualities of light were analyzed on ornamental specie of economic and commercial importance: Salvia splendens or Scarlet Sage (variety Red & White of PanAmerican Seeds©), using three different sources of artificial light (blue-LED, purple- LED and fluorescent) to modify the growth environment of each one. The investigation covered analysis of days to flowering, height, diameter, number of buds and SPAD values. Existing studies on the effect of spectral quality on plant growth show that exist significant alterations on variables in photomorphogenic and plant development. For example: the dry weight of the plant, height, internode length, number of buds, flowering duration, number of stomata per plant and amount of reducing sugars and starches. However, in this study it was found that the spectral quality provided with supplementary light only has effect in days to flowering compared with control treatment, because reduce in one week the flowering days, but, has not effect between supplementary lighting treatments. Others variables studied (buds number, height, diameter and values SPAD) had not significant effect by quality spectral used (p>0.05). The study was made in the academic greenhouse ITESM, located in Monterrey, Nuevo Leon, Mexico, during the period of August to December 2013.